Utilization of HIS Data and Associated Factors at Public Health Facilities of Sidama Regional State, Southern Ethiopia- Health Information Utilization at Public Health Facilities - Leda, Tegegn Tesema; Debiso, Alemu Tamiso; Alemayehu, Akalewold; Negeri, Keneni Gutema (The Ethiopian journal of health development, 2022)
Background: Health information plays a critical role in supporting evidence-based decision-making for all health system pillars. Although there have been marked improvements recently, routine health information utilization remains low in Ethiopia. Therefore, this study is designed to assess health information systems data utilization and the associated factors in Sidama Regional state, South Ethiopia. Methods: A facility-based cross-sectional study was conducted from December 2019 to December 2020 at public health institutions in the Sidama regional state, Southern Ethiopia. A systematic random sampling technique was used to select the study subjects. Data was collected using a structured, self-administered questionnaire through an interview and an observational checklist. The data were entered into EPIDATA version 3.5.3 and then exported to SPSS version 20 for analysis. Multivariable logistic regression was applied to identify factors associated with the utilization of health information systems. Results: The overall HMIS data utilization in the Sidama region was 57.8% (95% CI; 52.92, 62.68). HMIS data utilization was higher in hospitals (90%) than in health centers (48%). Receiving training on health management information systems (AOR =3.49; 95% CI, 1.89-6.70), data completeness (AOR, 2.98; 95% CI, 1.64-5.40), presence of eHMIS/computer (AOR, 2.53; 95% CI, 1.32-4.84), and having regular performance review on data use (AOR, 2.57; 95% CI, 1.43-4.63) were significantly associated with the utilization of health information system data. Conclusion: The overall HMIS data utilization in the Sidama region was low compared to the national figure. On-job HMIS training, the presence of electronic HMIS (eHMIS)/computer, data quality and regular standard performance reviews were key predictors of good data use practice. Therefore, it is recommended to train health staff on data quality and information use and improve information technology support to improve data utilization for HMIS.